Thematic Approach in Social Studies Learning to Increase Elementary School Student Activeness - Siagian, Yosua Marasi Parningotan (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This study investigates the application of a thematic approach in social studies learning to improve the activeness of elementary school students. This type of research uses an exploratory qualitative approach. The study was conducted at the YP HKBP Pematangsiantar Private Elementary School. The subjects in this study were fifth-grade students, class teachers, and the principal. Data were collected through observation, semi-structured interviews, and documentation, then analyzed using Miles and Huberman's interactive analysis technique. The results showed that before the thematic approach was implemented, social studies learning was monotonous and did not actively engage students. After the thematic approach was implemented, there was a significant increase in student activeness indicators, such as asking questions, answering questions, discussing in groups, and completing assignments independently. The thematic approach has been proven to be able to connect social studies material with students' real lives, thus creating a more enjoyable, contextual, and participatory learning atmosphere. These findings are supported by the theories of meaningful learning (Ausubel), constructivism (Vygotsky), and active involvement. This study recommends that teachers design social studies learning with a thematic approach in a structured and relevant manner to the students' local context. Research has proven that this approach fosters active student involvement and enhances the overall quality of the learning process at the elementary school level.